SAT0120 Mediators of Autonomic Neuropathy in Rheumatoid Arthritis. (10th June 2014) - Syngle, A.; Verma, I.; Krishan, P.; Garg, N.
Abstract : Background: Cardiovascular autonomic neuropathy (CAN) is a risk predictor for sudden cardiac death in rheumatoid arthritis (RA) 1 . RA is characterized by excess cardiovascular (CV) morbidity and mortality. Elevated interleukin (IL)-1β levels dampen vagal activity 2, interleukin (IL)-6 influence vagal tone 3 and anti IL-6 and tissue necrosis factor (TNF)-α improve autonomic dysfunction in RA -5 . Hence we decided to investigate mediators of autonomic neuropathy in RA. Objectives: To identify predictors of autonomic dysfunction among patients with RA. Methods: 25 adult patients with RA and 25 age and sex matched healthy controls were enrolled in the study. Autonomic function was assessed by cardiovascular reflex tests according to Ewing and peripheral sympathetic autonomic function was assessed by Sudoscan (Impeto Medical Device, EZS 01750010193 Paris, France). Biochemical estimation of Cytokines (Tumour necrosis factor (TNF)- α, Interleukin (IL)-6 and Interleukin (IL)-1) were measured by ELISA method. Biomarkers of inflammation erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) level were also estimated. Disease severity was assessed using the Disease Activity Score in 28 joints (DAS28). Results: RA patients had significantly impaired heart rate (HR) response to deep breath, HR response to standing, blood pressure (BP) response to hand grip and Sudoscan as compared to healthy controls (all p<0.05). Pro-inflammatory cytokines were significantly higher in RA as compared to healthy controls. TNF-α significantly correlated with HR response to deep breath, standing and Sudomotor function (Fig. 1A ), IL-6 significantly correlated with HR response to standing (Fig. 1B ), ESR significantly correlated with HR response to deep breath and standing, DAS28 also significantly correlated with HR response to deep breath in RA in univariate analyses. Conclusions: This study results suggests that autonomic function is impaired in RA. We identified a number of the risk predictors in this study included disease severity, ESR, TNF-α and IL-6. It is likely that the exposure to elevated cytokines associated with enhanced inflammatory state that characterizes RA leads to autonomic neuropathy in this disease. These results can be used to prospectively identify risk of autonomic dysfunction and sudden cardiac death in RA. Treatment with anticytokine drugs especially TNF-α inhibitor and IL-6 blockade could potentially be beneficial for treatment of autonomic dysfunction and its consequences in RA. References: Milovanovic B et al. Srp Arh Celok Lek. 2010; 138:26-32. Altawil R et al. Ann Rheum Dis. 2012;71 (Suppl 1): A1-A193. Sloan RP et al. Mol Med. 2007; 13:178–184. Syngle A et al. IJRCI. 2013; 1:CS7 Syngle A et al. Acta Reumato Port. 2013; 07-30. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5200